2023
DOI: 10.1038/s41598-023-47544-4
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of process parameters in micro-scale pneumatic aerosol jet printing for high-yield precise electrodes

Hakyung Jeong,
Jae Hak Lee,
Seungman Kim
et al.

Abstract: Aerosol jet printing (AJP) is a new non-contact direct writing technique designed to achieve precise and intricate patterns on various substrates. Specifically, the pneumatic AJP process breaks down the ink into fine particles, significantly reducing the risk of nozzle clogging and rendering it highly advantageous for industrial applications. This paper focuses on the optimization of the line electrode formation process using soluble silver clusters as the conductive ink, along with the aerosol formation proce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 55 publications
0
0
0
Order By: Relevance
“…Aerosol jet printing (AJP), a novel non-contact direct writing technique, is specifically designed to achieve precise and intricate patterns on a variety of substrates. 73 Parate et al 74 reported on an innovative aerosol-jet-printed (AJP) graphene-based immunosensor, which is capable of monitoring two distinct cytokines: interferon gamma (IFN-γ) and interleukin 10 (IL-10). To construct this sophisticated device, interdigitated electrodes (IDEs) were printed with a 40 μm finger width using graphene-nitrocellulose ink on a durable polyimide substrate.…”
Section: Porous Carbon From 3d Printingmentioning
confidence: 99%
“…Aerosol jet printing (AJP), a novel non-contact direct writing technique, is specifically designed to achieve precise and intricate patterns on a variety of substrates. 73 Parate et al 74 reported on an innovative aerosol-jet-printed (AJP) graphene-based immunosensor, which is capable of monitoring two distinct cytokines: interferon gamma (IFN-γ) and interleukin 10 (IL-10). To construct this sophisticated device, interdigitated electrodes (IDEs) were printed with a 40 μm finger width using graphene-nitrocellulose ink on a durable polyimide substrate.…”
Section: Porous Carbon From 3d Printingmentioning
confidence: 99%
“…While AJP technology presents numerous advantages, intricate interactions among the machine, process, and materials result in low controllability over the electrical performance of printed lines. This significantly affects the functionality of printed components, thereby limiting the broad applications of AJP 16 , 17 . As the AJP process exerts an indirect yet impactful influence on the electrical resistivity of printed lines via their effect on printed line morphology, researchers tend to optimize AJP process parameters, aiming to enhance the overall electrical performance of printed lines and broaden the applications of AJP.…”
Section: Introductionmentioning
confidence: 99%